Calidad de la educación: un desafío a cumplir - Martínez Ocaña, Bertha Emperatriz (2010)
The author clearly defines Educational Quality as that that satisfies basic learning needs; a type of education that includes learning, assimilating knowledge, doing, living with others, and being. Education should be oriented to fulfill the Right to Comprehensive and Quality Education. The author also points out some progress in the coverage of basic education in Peru emphasizing the pursuit of quality.